Optimization of MSMEs Revenue: The Key Role of Internal Control, Accounting Records, and Sustainability Performance in the Digital Era - Putri, Siara Zazkia Juliana; Nur Aisah; Norlela; Hanida, Rosiyana; Himawan, Hilmi Satria (Sustainability Accounting Journal, 2024)
According to the Ministry of Cooperatives and SMEs, based on data as of May 2022 there are around 65 million MSMEs in Indonesia. Palangka Raya City is one of the cities in Central Kalimantan Province whose people generally use MSMEs as one of the main sources of income to meet their living needs. One of them is Photocopy JB, whose business is selling decorative flowers, children's toys and women's fashion equipment. In running its business, Photocopy JB experienced several obstacles, namely market competition, implementation of internal controls, and not yet implementing an accounting recording system. The research method used is qualitative methods. Data processing in this research uses descriptive analysis methods. The research results show that Photocopy JB has not implemented good internal control because there are several internal control criteria that have not been met. Accounting records also do not apply the cash basis and accrual basis as well as SAK EMKM, while the use of social media as a promotional medium only uses Facebook which is promoted and only decorative flowers. The findings from this research are that the implementation of good internal controls can help MSMEs to prevent fraud, ensuring that financial transactions are carried out in accordance with applicable policies and procedures. Implementing adequate accounting records can help MSMEs to measure business performance, make business decisions, and reduce the risk of fraud. The use of social media in product promotion can help MSMEs to reach a wider target market and increase sales.